Business Dispute Resolution Through Arbitration Legal Remedies - Sarjono, Andrie Gusti Ari (Inspiring Law Journal, 2024)
Business activities always allow for a dispute (dispute/difference) between the parties involved. As a result of the dispute, the parties always want a quick resolution and settlement. Delays in resolving trade disputes will result in inefficient economic development, decreased productivity, and conversely increased production costs. This not only hinders the improvement of workers' welfare and progress, but also harms consumers. Arbitration is a very simple and informal method of dispute resolution, which is essentially private. The simplicity of Arbitration is reflected in its process: the disputing parties agree to submit their dispute to a person who is recognized by both parties as having expertise and wisdom, this person is called the Arbitrator. The Arbitrator listens to arguments from both parties, considers the facts and arguments presented, and ultimately renders a decision. In essence, the purpose of the parties in resolving disputes through Arbitration is to find a solution that is beneficial to all parties, maintain the confidentiality of their dispute, and achieve a resolution that is fast, efficient, and does not take a long time. The parties who resolve this dispute usually have expertise in their fields and their integrity has been tested, and they maintain neutrality